2010
DOI: 10.1002/ep.10484
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of unhairing effluents by activated sludge system

Abstract: The unhairing step in leather manufacture generates a highly hazardous and alkaline wastewater. This article reports the evaluation of an activated sludge system for the treatment of unhairing wastewater and effluent detoxification, assessed by seed germination tests.The activated sludge system reactor was fed for 112 days with diluted unhairing effluent; the operation strategy included increasing the organic loading rate (OLR) from 0.7 to 1.6 g chemical oxygen demand (COD) L 21 d 21 . COD and suspended solids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In previous work, we compared the performances of aerobic tank reactors for treatment of unhairing wastewater . As the structure and dynamics of the microbial community in the biological processes applied to tannery wastewater are poorly understood, we report the results of an investigation into the structure and dynamics of key functional groups in the microbial communities of activated sludge and endogenous biomass reactors.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we compared the performances of aerobic tank reactors for treatment of unhairing wastewater . As the structure and dynamics of the microbial community in the biological processes applied to tannery wastewater are poorly understood, we report the results of an investigation into the structure and dynamics of key functional groups in the microbial communities of activated sludge and endogenous biomass reactors.…”
Section: Introductionmentioning
confidence: 99%
“…Although no characterization of organic pollutants was carried out in this study, previous studies reported the profile of organic and inorganic compounds in tannery effluents. According to Mlaik et al [20], UE contains high organic load, lime, and sodium sulfide since they are used during liming-unhairing operation. Also, Mlaik et al [58] pointed to the presence of many hydrocarbons, including saturated (C16:0, C18:0) and unsaturated fatty acid methyl esters as well as long- and short-chain alkenes in the UE.…”
Section: Resultsmentioning
confidence: 99%
“…For all samples, seedling phytotoxicity was measured using different dilutions of raw and treated effluent samples (10, 20, 50, and 100%). Dilutions were chosen based on some literature studies, especially those of Mlaik et al [20], and also on our preliminary assays in which we found that 30% was nearly the same as 20% and 40% gives very similar results to those of 50%. For proportions from 60% to 90%, there was a high inhibition level of the germination seeds; that's why these proportions were not mentioned.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the biological approach that combines anaerobic and aerobic processes can be advisable as a handy tool for removing organics from LFL pretreated with air stripping method. Among the main aerobic treatments, we can highlight activated sludge [22], biofilters [23] and rotating biological contactors [24].…”
Section: Introductionmentioning
confidence: 99%